Leukocyte Telomere Length at Birth and During the Early Life of Children Exposed to but Uninfected With HIV After In Utero Exposure to Antiretrovirals - Ajaykumar, Abhinav (J Infect Dis, 2018)
BACKGROUND: Maternal combination antiretroviral therapy (cART) during pregnancy could impact the health of human immunodeficiency virus (HIV)–exposed, HIV-uninfected (HEU) children, because some antiretrovirals cross the placenta and can inhibit telomerase. Our objective was to compare leukocyte telomere length (LTL) in HEU children and HIV-unexposed, HIV-uninfected (HUU) children at birth and in early life and to investigate any relationship with cART exposure. METHODS: HEU and HUU children’s blood LTL was compared cross-sectionally at birth, and during the first three years of life. Longitudinal HEU LTL dynamics was evaluated over that same period. RESULTS: At birth, the LTL in HEU children (n = 114) was not shorter than that in HUU children (n = 86), but female infants had longer LTL than male infants. Maternal cART (duration or type) showed no association with shorter infant LTL. Among 214 HEU children age- and sex-matched at a 1:1 ratio to HUU children, LTL declined similarly in both groups. In a longitudinal analysis, LTL attrition in HEU children was rapid from birth to 1 year of age and gradual thereafter. Zidovudine prophylaxis did not significantly alter LTL. CONCLUSIONS: Our results indicate that from birth to 3 years of age, the LTL in HEU children is not negatively affected by exposure to maternal HIV infection and cART, at least not to the regimens used within this Canadian cohort, a reassuring finding.